2012
DOI: 10.1109/tns.2012.2202918
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study to Optimize SiPM Photo-Detectors for Highest Time Resolution in PET

Abstract: We report on a systematic study of time resolution made with three different commercial silicon photomultipliers (SiPMs) (Hamamatsu MPPC S10931-025P, S10931-050P, and S10931-100P) and two LSO scintillating crystals. This study aimed to determine the optimum detector conditions for highest time resolution in a prospective time-of-flight positron emission tomography (TOF-PET) system. Measurements were based on the time over threshold method in a coincidence setup using the ultrafast amplifier-discriminator NINO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…On the opposite detector arm, a reference LYSO-crystal of mm was mounted and fully wrapped with Teflon and coupled with Rhodorsil optical glue to a similar MPPC. The front-end electronics are based on the time-over-threshold method using the fast and low noise NINO discriminator as described in [12].…”
Section: Resultsmentioning
confidence: 99%
“…On the opposite detector arm, a reference LYSO-crystal of mm was mounted and fully wrapped with Teflon and coupled with Rhodorsil optical glue to a similar MPPC. The front-end electronics are based on the time-over-threshold method using the fast and low noise NINO discriminator as described in [12].…”
Section: Resultsmentioning
confidence: 99%
“…Expressed in terms of coincidence time resolution (CTR) and FWHM, relation (4) then becomes: (5) It must be noted, however, that in the context of overall timing resolution this approximation is a simplification as, e.g., SiPM transit time spread, being typically of order hundred picoseconds, is totally neglected in this picture [23], [24]. The aim of this paper, however, is to concentrate on scintillators and ascertain their trends in CTR irrespective of other instrumental influences, albeit shown in a separate work by Gundacker et al [8]. Hence, Fig.…”
Section: A Photostatisticsmentioning
confidence: 99%
“…3. Only one type of SiPM was used in two identical back-to-back detector arms, i.e., the Hamamatsu-MPPC S10931-050P, with a SPAD size of 50 m. From an earlier study [8] it was found to be the fastest for these purposes. The operating bias of this SiPM, optimized for highest time resolution, was 72.4 V, 2 V above the measured breakdown voltage.…”
Section: Experimental Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…A coincidence timing resolution of 101 ps FWHM was achieved with LaBr 3 :Ce crystals of 3 × 3 × 5 mm 3 size coupled to Hamamatsu MPPCs 3 × 3 mm 3 [25]. With Cerium and Calcium co-doped LSO (LSO:CeCa) crystals, 2 × 2 × 20 mm 3 also coupled to Hamamatsu MPPCs 3 × 3 mm 3 , a 170 ps FWHM resolution has been obtained employing the NINO ASIC for readout [26].…”
Section: Medical Applicationsmentioning
confidence: 99%